The effect of iron status on gadolinium deposition in the rat brain: mechanistic implications - Prybylski, John P.; Jastrzemski, Olivia; Jay, Michael (Frontiers in Toxicology, 2024)
Introduction: Sites associated with gadolinium (Gd) deposition in the brain (e.g., the globus pallidus) are known to contain high concentrations of ferric iron. There is considerable debate over the mechanism of Gd deposition in the brain. The role of iron transport mechanisms in Gd deposition has not been determined. Thus, we seek to identify if Gd deposition can be controlled by modifying iron exposure.Methods: Female Sprague-Dawley rats were given diets with controlled iron levels at 2–6 ppm, 6 ppt (20 g/kg Fe carbonyl) or 48 ppm for 3 weeks to induce iron deficiency, overload or normalcy. They were kept on those diets while receiving a cumulative 10 mmol/kg dose of gadodiamide intravenously over 2 weeks, then left to washout gadodiamide for 3 days or 3 weeks before tissues were harvested. Gd concentrations in tissues were analyzed by ICP-MS.Results: There were no significant effect of dietary iron and total Gd concentrations in the organs, but there was a significant effect of iron status on Gd distribution in the brain. For the 3-week washout cohort, there was a non-significant trend of increasing total brain deposition and decreasing dietary iron, and about 4-fold more Gd in the olfactory bulbs of the low iron group compared to the other groups. Significant brain accumulation was observed in the low iron group total brain Gd in the 3-week washout group relative to the 3-day washout group and no accumulation was observed in other tissues. There was a strong negative correlation between femur Gd concentrations and concentrations in other organs when stratifying by dietary iron.Discussion: Gd brain deposition from linear Gd-based contrast agents (GBCAs) are dependent upon iron status, likely through variable transferrin saturation. This iron dependence appears to be associated with redistribution of peripheral deposited Gd (e.g., in the bone) into the brain.